Low Frequency of SV40, JC and BK Polyomavirus Sequences in Human Medulloblastomas, Meningiomas and Ependymomas - Weggen, Sascha (Brain Pathol, 2006)
Several reports have suggested a role for polyomaviruses in the pathogenesis of human brain tumors.This potential involvement is not conclusively resolved. For the present study, a highly sensitive PCR‐assay with fluorescence‐labelled primers was developed to search for polyomavirus sequences in human brain tumor and control DNA samples. The assay was shown to detect approximately one viral large T‐antigen (TAg) gene per 250 cells. We identified simian virus 40 (SV40)‐like sequences in 2/116 medulloblastomas, in 1/131 meningiomas, in 1/25 ependymomas and in 1/2 subependymomas. A single case of ependymoma contained SV40 VP‐1 late gene sequences. Moreover, one of the meningioma samples showed JC virus sequences. In contrast, 60 hepatoblastoma samples and 31 brain samples from schizophrenic patients were consistently negative. BK virus sequences were not detectable in any of our samples. Immunohistochemical analysis of two SV40 positive tumor biopsies failed to detect large TAg in the tumor cells. In the JC positive meningioma, immunoreactivity for the viral late gene product (VP‐1) was not observed. Our data do not entirely rule out SV40 and JC virus as an initiative agent with a hit‐and‐run mechanism. However the low frequency of virus sequences and the absence of TAg protein expression argue against a major role of these viruses in the pathogenesis of human medulloblastomas, meningiomas and ependymomas.